If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 6 + 3 * -4 * -2 Multiply 3 * -4 x = 6 + -12 * -2 Multiply -12 * -2 x = 6 + 24 Combine like terms: 6 + 24 = 30 x = 30 Solving x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 30
| 3+5w=-17 | | 1/2(1/2^n) | | 40-4x16/2 | | 6(-7-5)=-42 | | x=6+3(-4)-2 | | (3q-8)(4w-1)(-3w+5)=0 | | (5x-5)(4x-2)= | | -7x-3x-2=-8x-8 | | 3x+3(x-2)=5x-21+2x | | -5(5y-10)-y=-3(y-4) | | 25=12/x | | 16-10= | | 3(y+8)-2(y-5)=3(y-3) | | 40-4x16/2=8 | | 10x+16=3(3x+3) | | X=11-4y | | 4(b+3)-(2b)=26 | | 4480=x(82000-x) | | x^2=288-2x | | 12r-4=7+12r | | h-2-3= | | n/43 | | -5(2n+6)=-90 | | x=12-0.25(-4) | | 6x-8-2x=x+2+x | | 3a-3=0 | | 1/2(-24+60)= | | (8)+7w=43 | | 16x/20x^3 | | b/313 | | s/216 | | 5x+3=6x-8 |